Enkripsi Data Citra untuk Model Warna RGB dan Treshold Menggunakan Algoritma Hill Cipher - Ommi Alfina (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2019)
With the increasingly widespread abuse of digital media, especially in the form of images or images, it increasingly disrupts the rights and privacy of everyone. Many forms of abuse that occur in digital media through internet facilities such as plagiarism of photographer#39;s work, recognition of the rights of the image, to upload photos of privacy to internet media. Therefore, one way to secure digital data in the form of images is to randomize (encrypt) the images that we feel are very important so that the image can no longer be interpreted by others. If we need these data, we just need to return it (decryption) so that the encryption image can return to its original form. Hill Cipher algorithm is one method to randomize a data by encoding and multiplying the matrix. For its application in the form of image data, a trial is needed by creating a software which will then analyze the results into several color models such as RGB, Grayscale (Keabuan) and Tresholding (Black and White). From the test results, it can be concluded that the greater the input matrix value of the Hill Cipher Algorithm, the more encrypted image results will be obtained or in other words the more incomprehensible the visual form by humans. Then the Hill Cipher algorithm cannot be applied to the color threshold model (black and white) because the matrix multiplication obtained does not have a diverse range of values